Social affordances of agile governance - Ines Mergel (Public Administration Review, 2023)
Agile refers to a work management ideology with a set of productivity frameworks that support continuous and iterative progress on work tasks by reviewing one's hypotheses, working in a human-centric way, and encouraging evidence-based learning. In practice, public administrations have started to use agile principles and methods to plan projects, work in short sprints, iterate after receiving feedback from stakeholders, and apply a human-centric approach to arrive at prototyped solutions. To understand the opportunities and challenges public servants perceive when they are asked to apply agile work practices, I conducted focus groups to study the social affordances of agile governance that need to be in place for public servants to adopt an agile mindset and its related practices. As a result of the exposure to agile work practices, public servants are either able to perceive its affordances and are willing to adopt agile, they falsely perceive them or they even remain hidden from them leading to a rejection of agile.
Keywords: 340